PEEK Material in the Reconstruction of Maxillofacial Defects: A Literature Review - Koroglu, Merve Nur; Tekin, Samet (Mesut TUZLALI, 2025)
Congenital or acquired maxillofacial defects cause aesthetic, phonetic, functional and psychological problems. These multiple problems create various treatment alternatives for the rehabilitation of the defect area. The success of the prosthetic treatment applied in the reconstruction of the defect directly affects patient satisfaction and quality of life. The main aim of prosthetic rehabilitation is to reconstruct the defects and eliminate the associated problems. Material selection in prosthetic treatment is important in terms of patient comfort and acceptability. The main properties desired in this selection are biocompatibility, durability, lightness, shaping capability, thermal resistance, radiolucency and low infectivity. Silicone-based materials, methyl methacrylate, titanium mesh and polyethylene are the materials commonly used in the reconstruction of defects with their advantages and disadvantages. As a result of the search for the ideal material, Polyetheretherketone (PEEK) is thought to be an alternative material. This review discusses the use of PEEK for prosthetic rehabilitation in patients with maxillofacial defects.

Doğumsal veya kazanılmış maksillosiyal defektler estetik, fonetik, fonksiyonel bozukluklar ve psikolojik problemlere sebep olur. Çok yönlü problemler defekt bo?lgesinin rehabilitasyonu ic?in c?es?itli tedavi alternatifleri oluşturur. Defektin rekonstrüksiyonda uygulanan protetik tedavinin başarısı hasta memnuniyetini ve yaşam kalitesini doğrudan etkilemektedir. Protetik rehabilitasyonun primer amacı defektleri kapatmak ve buna bağlı problemleri ortadan kaldırmaktır. Protetik tedavide malzeme seçimi hasta konforu ve kabullenebilirlik açısından önemlidir. Bu seçimde istenilen başlıca özellikler biyouyumluluk, dayanıklılık, hafiflik, şekillendirilebilme imkanı, termal dayanım, radyolüsentlik ve düşük enfeksiyona sebebiyet verebilmesidir. Defektlerin rekonstrüksiyonunda silikon esaslı materyaller, metil metakrilat, titanyum ağ ve polietilen (PE) avantaj ve dezavantaları ile rutinde kullanılan materyallerdir. İdeal malzeme arayışının neticesinde Polietereterketonun (PEEK) alternatif bir materyal olabileceği düşünülmektedir. Bu derlemede maksillofasiyal defekte sahip hastalarda protetik rehabilitasyon amaçlı kullanılan PEEK’in avantaj ve dezavantajlarından bahsedilecektir.
Maksillofasiyal Defektlerin Rekonstrüksiyonunda PEEK Materyalinin Yeri: Bir Literatür Derlemesi
Keywords: Prosthodontics; Protez